Analysis of the upper and lower limbs movement in elite fencing attack skills - Kim, T.; Choi, S. (Korean Journal of Sport Science, 2021)
PURPOSE: This study aims to help improve performance by comparing and analyzing the kinematic variables for each upper and lower extremities segment when two groups of players attack the national women`s fencing players in a match situation. METHODS: This study divided the movement time, movement time ratio, Fente step length change, angle factor at each event, and velocity factor of the fencing point of a sword at each event into the Olympic medalists` group (Group A) and the international competition winners group (Group B) during the fencing Marche Fente. An independent t-test was performed for each factor, and the results were compared. RESULTS: As a result, the difference between the two groups in movement time was statistically significant in the front of the foot in the velocity factor. However, no statistical significance was found between the two groups in the front angle of the trunk, the elbow angle, and the knee angle. CONCLUSIONS: This indicates that group A and group B are both outstanding players with the best performance, so they are similar in the details of the movements except for the very slight difference in time and velocity. Therefore, the average of the result values of the joint angle will be a feedback index for fencing beginners or education subjects who are now starting to fencing.